2020
DOI: 10.1007/978-1-0716-0644-5_36
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Genetic Assays for the Study of DNA Joint Molecules Metabolism and Multi-invasion-Induced Rearrangements in S. cerevisiae

Abstract: DNA double-strand breaks (DSBs) are genotoxic lesions that can be repaired in a templated fashion by homologous recombination (HR). HR is a complex pathway that involves the formation of DNA joint molecules (JMs) containing heteroduplex DNA. Various types of JMs are formed throughout the pathway, including Displacement loops (D-loops), multi-invasions (MI), and double Holliday Junction intermediates. Dysregulation of JM metabolism in various mutant contexts revealed the propensity of HR to generate repeat-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…MIs are readily formed in reconstituted in vitro reactions with ssDNA substrates of physiological length ( i.e. >100 nt) and yeast and human Rad51, Rad54, and RPA proteins, and in S. cerevisiae cells (Piazza et al 2017; Wright and Heyer 2014; Piazza et al 2021b). They are presumably byproducts of homology search by inter-segmental contact sampling demonstrated for RecA (Forget and Kowalczykowski 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MIs are readily formed in reconstituted in vitro reactions with ssDNA substrates of physiological length ( i.e. >100 nt) and yeast and human Rad51, Rad54, and RPA proteins, and in S. cerevisiae cells (Piazza et al 2017; Wright and Heyer 2014; Piazza et al 2021b). They are presumably byproducts of homology search by inter-segmental contact sampling demonstrated for RecA (Forget and Kowalczykowski 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The translocation assay has been described previously (Piazza et al 2017(Piazza et al , 2021b. Briefly, the basal Lys + frequency was determined by plating yeast cells exponentially growing in YEP-lactate liquid culture on SD-LYS and YPD plates (control plating).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DSB ends are resected first by the Mre11-Rad50-Xrs2 NBS1 (MRX) complex, but more extensive 5' to 3' resection depends on two other exonucleases, Exo1 or the Sgs1-Rmi1-Top3-Dna2 complex, to create long single-stranded 3'-ended tails (13). These strands are first bound by the single-strand DNA binding complex, RPA, and then by the Rad51 recombinase that initiates the search for homology and the repair of the DSB by homologous recombination (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…During the homology-mediated strand invasion, it has been reported that the end of the single-strand DNA is not necessary for the strand exchange ( Wright and Heyer 2014 ; Piazza et al 2017 , 2021 ; Piazza and Heyer 2018 ). So the large 3’ overhang generated by DSB end resection might invade into multiple template DNA and form a multi-invasion joint molecule ( Piazza and Heyer 2019 ).…”
Section: Introductionmentioning
confidence: 99%